GEOLOGICAL AND ECONOMIC ASSESSMENT OF COAL DEPOSITS: CONTRASTING NATIONAL AND INTERNATIONAL TAXONOMIES IN ESTIMATING RESERVES AND RESOURCES - Rudko, G.; Kurylo, M.; Bala, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of the study is to examine major differences and similarities in domestic and international methodological approaches to estimating mineral resources base and assessing coal deposits. There is carried out a contrastive analysis of taxonomic criteria for coal deposits based on National Regulations and Australian Guidelines for Estimation and Classification of Coal Resources. Coal reserves having been analyzed in terms of quality and quantity (basic evaluation criteria) and factors that determine their commercial value having been identified, there is revealed a sufficient level of compliance with these criteria. However, there have been noticed cases of mismatch between assessable objects and their taxonomic nests, and hence, the suggestion is made to appropriate available geological information to every classifiable case. The study of the Guidelines reveals awareness of geological environment, commercial significance, and the extent of the feasibility analysis carried to be primary assessment criteria. The main differences in the criteria are recognized to lie in methods that validate assessment, for which direct statistical analysis and geo-statistical modeling of deposits are used in international practice. The practicability of the analysis suggested results in optimizing geological and economic evaluation of coal deposits by unifying different criteria. In the research there are compared the following options: Resource Categories (Measured, Indicated, Inferred Resources); Reserves Categories: A + B + C1 + C2; and Coal Reserves Categories, which are proven reserves. Comparison of the first group of quantitative indicators shows almost a complete match in volumes of previously explored and prospected reserves within all categories of Coal Resources. For categories of Coal Reserves and proven reserves there are significant differences resulting from the application of modifying factors to their definition in the case of JORC terminology. Coal Reserves values are more in line with quantity of commercial (recoverable) reserves - part of balance reserves, which are extracted taking into account project losses. In this case, quantity of recoverable reserves significantly exceeds Coal Reserves quantity. This is due to the fact that in national practice commercial reserves are assessed based on all quantity of previously explored and prospected categories, and Coal Reserves categories are based on the most reliable quantity of Indicated and Measured Resources.